2011
DOI: 10.1108/10650741111181616
|View full text |Cite
|
Sign up to set email alerts
|

Health data standards and adoption process

Abstract: Purpose -This paper seeks to carry out a critical study of health data standards and adoption process with a focus on Saudi Arabia. Design/methodology/approach -Many developed nations have initiated programs to develop, promote, adopt and customise international health data standards to the local needs. The current status of, and future plans for, health data and related standards in developing countries are still questionable due to the absence of government actions, plans and related studies. However, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In [19] concluded that, health sector in Saudi Arabia was not ready for implementing successful HIS. In another study, [20] found that 18 factors were seriously influencing the adoption of HIS in Saudi Arabia such as external pressure, network externalities, cost and standards characteristics including the industrial technical standards such as usability and quality.…”
Section: Current Issues Of His Usabilitymentioning
confidence: 99%
“…In [19] concluded that, health sector in Saudi Arabia was not ready for implementing successful HIS. In another study, [20] found that 18 factors were seriously influencing the adoption of HIS in Saudi Arabia such as external pressure, network externalities, cost and standards characteristics including the industrial technical standards such as usability and quality.…”
Section: Current Issues Of His Usabilitymentioning
confidence: 99%
“…From the literature, one perceives that the notion of IT complexity, rather than being an absolute technical characteristic, is more contingent upon the adopting organization. It refers to the relative perception of potential adopters as to the ease with which IT‐related standards can be understood, and then be implemented and used (Alkraiji et al , 2010). There exists a negative relationship between the perceived complexity of e‐learning technology and the firm's decision to adopt it (Hsbollah and Idris, 2009).…”
Section: Research Framework and Propositionsmentioning
confidence: 99%
“…We investigated the relationships between the adoption of an EDR as a DIT tool and region, practice size, and practice type [ 5 ]. Our study attempted to identify the practice characteristics that predict EDR adoption; because the concept of EHRs is relatively new in SA [ 14 , 23 ] our findings could add valuable insights into developing effective strategies to encourage healthcare providers to adopt EDRs.…”
Section: Discussionmentioning
confidence: 99%